Effectiveness of the In-On-In Service Learning Pattern Workshop on Teacher Digital Competence - Jamaluddin, Wahida (Program Studi Pendidikan Profesi Guru Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2024)
Educators' digital competence is closely related to educators' skills in using information and communication technology based on pedagogical principles while being aware of the implications for education methodology. This research aims to analyze teacher digital competence through in-on-in service learning pattern workshops. This type of research is a one-way experiment. The data collection technique used in this research is in the form of a questionnaire or questionnaire in the form of questions on Google Form. Based on data analysis that was carried out from 40 respondents and the results of supervision during classroom learning. The research results revealed that increasing teacher competency through in-on-in pattern workshops is important in supporting the implementation of the learning process. The trial results also stated that the media developed as a result of this workshop is very suitable for use in the learning process. The results of the pre-test questionnaire of 40 respondents at Madrasah Tsanawiyah Negeri Gowa answered that in-on-in learning service pattern workshops, 40% of teachers were happy and could use learning media in the teaching and learning process and 45% said they needed media in PBM, the types of media used included PPT , Canva, Quiziz, Google site, 40% can increase motivation, interest and learning outcomes of students at Madrasah Tsanawiyah Negeri Gowa. Posttest from the results of 40 respondents at the Gowa State Madrasah Tsanawiyah answered that the in-on-in learning service pattern workshop 97.5% of teachers were happy and could use learning media in the teaching and learning process and 92.5% said they needed media in PBM, types of media used include PPT, Canva, Quiziz, Google site. 100% can increase motivation, interest and learning outcomes of students at the Gowa State Tsanawiyah Madrasah.